Pengetahuan dan Sikap Mahasiswa Keperawatan terhadap Protokol Kesehatan di Masa New Normal - Zuhana Zuhana; Sintiya Halisya Pebriani; Adi Saputra (Politeknik Kesehatan Tanjung Karang, 2021)
The spread of the covid-19 virus can be prevented by implementing health protocols such as washing hands regularly or using a hand sanitizer, using a mask, applying cough etiquette, and maintaining physical distance and social distancing. The purpose of this study was to determine the relationship between knowledge and attitudes on the implementation of health protocols in nursing students of STIK Siti Khadijah Palembang. The design of this study used a descriptive correlation method with a cross-sectional approach, a total sample of 191 respondents with a total sampling technique, and the data were analyzed using the Spearman Rank (Rho). Data collection using an online-based questionnaire (google form) regarding knowledge, attitudes, and actions regarding the implementation of health protocols. The results of the analysis showed that there was a positive correlation between knowledge and attitudes toward the implementation of health protocols (p-value=0,007; r=0,248; p-value=0,001; r=0,301). Compliance with health protocols during the new normal period is very important to break the chain of the spread of the covid-19 virus.